Supportive policy environment on informal seed system led to increased utilization of local climate-resilient varieties in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Bioversity International has established community seedbanks to enable farmers to have easy access to diverse, good quality seed, conserve it and commercialize it for improved livelihoods. In Uganda, for some years, Bioversity International advocated for the formal recognition of community seedbanks and farmers varieties. The revised Seed Policy (2018) published in 2019 recognizes these efforts and has provisions for strengthening community seedbanks, and for production and commercialization of quality declared seeds in the informal system, in favor of smallholder farmers.